Third Trimester Vitamin D Status Is Associated With Birth Outcomes and Linear Growth of HIV-Exposed Uninfected Infants in the United States. (1st July 2019) - Sudfeld, Christopher R.; Jacobson, Denise L.; Rueda, Noé M.; Neri, Daniela; Mendez, Armando J.; Butler, Laurie; Siminski, Suzanne; Hendricks, Kristy M.; Mellins, Claude A.; Duggan, Christopher P.; Miller, Tracie L.
Abstract : Background: Vitamin D status in pregnancy may influence the risk of prematurity, birth size, and child postnatal growth, but few studies have examined the relationship among pregnant women living with HIV. Methods: We conducted a prospective cohort study of 257 HIV-infected mothers and their HIV-exposed uninfected infants who were enrolled in the 2009–2011 nutrition substudy of the Surveillance Monitoring for ART Toxicities (SMARTT) study. HIV-infected pregnant women had serum 25-hydroxyvitamin D (25(OH)D) assessed in the third trimester of pregnancy, and their infants' growth and neurodevelopment were evaluated at birth and approximately 1 year of age. Results: The mean third trimester serum 25(OH)D concentration was 35.4 ± 14.2 ng/mL with 15% of women classified as vitamin D deficient (<20 ng/mL) and 21% as insufficient (20–30 ng/mL). In multivariable models, third trimester vitamin D deficiency and insufficiency were associated with −273 g [95% confidence interval (CI): −450 to −97] and −203 g (95% CI: −370 to −35) lower birth weights compared with vitamin D sufficient women, respectively. Maternal vitamin D deficiency was also associated with shorter gestation (mean difference −0.65 weeks; 95% CI: −1.22 to −0.08) and lower infant length-for-age z-scores at 1 year of age (mean difference: −0.65; 95% CI: −1.18 to −0.13). We found no association of vitamin D status with infant neurodevelopment at 1 year of age. Conclusion: Third trimester maternal vitamin D deficiency was associated with lower birth weight, shorter length of gestation, and reduced infant linear growth. Studies and trials of vitamin D supplementation in pregnancy for women living with HIV are warranted. Abstract : Supplemental Digital Content is Available in the Text.